2014
DOI: 10.1371/journal.pone.0109213
|View full text |Cite
|
Sign up to set email alerts
|

Protospacer Adjacent Motif (PAM)-Distal Sequences Engage CRISPR Cas9 DNA Target Cleavage

Abstract: The clustered regularly interspaced short palindromic repeat (CRISPR)-associated enzyme Cas9 is an RNA-guided nuclease that has been widely adapted for genome editing in eukaryotic cells. However, the in vivo target specificity of Cas9 is poorly understood and most studies rely on in silico predictions to define the potential off-target editing spectrum. Using chromatin immunoprecipitation followed by sequencing (ChIP-seq), we delineate the genome-wide binding panorama of catalytically inactive Cas9 directed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
89
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 33 publications
13
89
0
Order By: Relevance
“…Our findings provide direct evidence to support previous speculation that Cas9 relies on protospacer sensing to enable accurate targeting 21,22 . In particular, we propose that REC3 binding to the RNA-DNA duplex is necessary for re-orienting REC2, which enables HNH docking at the active site (Extended Data Figure 4h–i).…”
supporting
confidence: 89%
“…Our findings provide direct evidence to support previous speculation that Cas9 relies on protospacer sensing to enable accurate targeting 21,22 . In particular, we propose that REC3 binding to the RNA-DNA duplex is necessary for re-orienting REC2, which enables HNH docking at the active site (Extended Data Figure 4h–i).…”
supporting
confidence: 89%
“…Although the Cas9-sgRNA complex can bind many off-target sites (56,76,106), with some bearing seed sequences as short as just 5 nt (76,106), only a small fraction of off-target sequences are cleaved (56,106), suggesting that DNA binding per se is insufficient to trigger cleavage of DNA substrates (9). The uncoupling of DNA binding and cleavage indicates that the prokaryotic CRISPR-Cas9 system may use a multistep mechanism for degradation of foreign DNA.…”
Section: Decoupled Dna Binding and Cleavage Eventsmentioning
confidence: 99%
“…The uncoupling of DNA binding and cleavage indicates that the prokaryotic CRISPR-Cas9 system may use a multistep mechanism for degradation of foreign DNA. Indeed, both in vitro and in vivo cleavage assays demonstrate that complementary base pairing at the PAM-distal end is critical for Cas9 cleavage activity (9,24,93). Bulk fluorescence resonance energy transfer (FRET) experiments further suggest that the conformational state of the HNH nuclease domain, which is driven by RNA-DNA hybridization and particularly sensitive to PAM-distal-end complementarity, allosterically controls RuvC activity to ensure accurate, concerted target DNA cleavage (93).…”
Section: Decoupled Dna Binding and Cleavage Eventsmentioning
confidence: 99%
“…It has been shown that dCas9 binds to off-target sites although affinity to those sites might be weaker than that to the target sites [22][23][24][25] . There are several ways to manage contamination of molecules bound to those off-target sites.…”
Section: Discussionmentioning
confidence: 99%